Multiparametric MR Imaging Features of Primary CNS Lymphomas - Talybov, Rustam; Beylerli, Ozal; Mochalov, Vadim; Prokopenko, Alexey; Ilyasova, Tatiana; Trofimova, Tatiana; Sufianov, Albert; Guang, Yang (Frontiers in Surgery, 2022)
Objective: Our aim was to indicate the insufficient effectiveness of the MR / CT perfusion technique as a part of multiparametric imaging in the differential diagnosis of primary CNS lymphoma (PCNSL) and high-grade gliomas or metastatic lesions. Materials and Methods: We described ten patients with primary CNS lymphoma presented high value of rCBV. Seven cases IHC-proved. Patients underwent CT perfusion imaging (Canon Aquilion One, Iomeron 400 mg – 50 ml) and DSC perfusion imaging (General Electric Discovery W750 3T, Gadovist 7.5 ml). Immunohistochemistry markers list includes: СD3, CD20, CD34, Ki-67, VEGF. Results: Classic and atypical radiographic features of the PCNSL, diagnostic capabilities of the MR / CT perfusion technique were described. Conclusion: Our cases suggest perfusion imaging has not proven efficiency for reliable differential diagnosis in context of primary CNS lymphoma, high-grade glioma (grade 3-4 WHO 2016) and metastatic tumors.